Compact groups of galaxies in GAMA - Zandivarez, Arnaldo Ariel (2024)
Context. Over the years, several compact group catalogues have been constructed using different methods, but most of them are not deep enough to go beyond the very local universe with a high level of redshift completeness. Aims. We proposed to build a statistically reliable sample of compact groups to study the influence of its inner extreme environment at intermediate redshifts. Methods. We adopted the Galaxy And Mass Assembly redshift survey as a parent galaxy catalogue, complemented with a small sample of galaxies from the Sloan Digital Sky Survey, to identify compact groups using Hickson-like criteria. We explored the parameter space to perform several identifications to build samples with different characteristics. Particularly, we reduced the maximum galaxy separation in the line-of-sight to 500 km s−1 and we implemented different magnitude ranges to define membership: 3, 2 or 1 magnitude difference between the brightest galaxy and the other members, and no restriction at all. For comparison, we used control samples extracted from a catalogue of loose groups to contrast properties with the compact groups. Results. We build five considerably large compact group samples, ranging from more than 400 up to roughly 2400 systems, and maximum redshifts from 0.2 to 0.4, depending on the selected parameters. The overall properties of each sample are in agreement with previous findings. Moreover, there is a tendency of compact groups to have a larger fraction of quenched galaxies than control loose groups, mainly for low stellar mass galaxies in compact groups with small crossing times. In addition, ∼ 45% of compact groups are embedded in loose galaxy systems and display the highest compactness, lowest crossing times and brightest first-ranked galaxies compared to compact groups considered non-embedded or isolated. There is almost no evolution of compact group properties with redshift. Conclusions. Our results confirm previous findings that postulate compact groups as one of the suitable places to study the suppression of the star formation rate in galaxies primarily due to galaxy interactions. These new Hickson-like compact group samples will be valuable to deepen the analysis of these peculiar galaxy systems in a redshift regime poorly explored so far.